Adicción a internet y su relación con factores familiares en adolescentes de 15 a 19 años en la ciudad de Loja. - Aponte Rueda, Deyvar Ronal (2017)
Internet currently plays a key role in many aspects of our lives. However, its frequent use has led to addiction problems, especially in vulnerable groups such as adolescents. There is still little data on the relationship between this type of dependence and family factors. The objective of this study was to assess internet addiction and family factors in adolescents. The study was cross-sectional, descriptive and analytical. It was carried out in high schools located in the city of Loja, Ecuador. The study population comprised 388 adolescents aged 15-19 years old who were chosen via the application of a stratified randomization method within the high schools. A sociodemographic and family characterization questionnaire, a socioeconomic stratification questionnaire, a perception test of family functionality (FFSIL) and a Young Internet Addiction Test (IAT) were all used. The results obtained showed that adolescents suffering from internet addiction who came from small families (p <0.002) and from a typical socioeconomic stratum (p <0.025) had more family dysfunctionality and that social networks were what they mostly used (P <0.034.). A greater level of internet addiction (IA) was found among adolescents attending the first year of high school (p <0.003), those using the internet for more than 17 hours per week (p <0.008) and those with good living conditions (p <0.005). Within the dimensions of family functionality, a higher IA was observed in adolescents with low cohesion (p <0.028), low harmony (p <0.0001), low affectivity (p <0.023) and low communication (p <0.021). It was concluded that adolescents with family dysfunction, who come from small families and have a typical socioeconomic stratum plus use social networks more, are at greater risk of suffering from internet addiction. The same occurs in adolescents with low levels of cohesion, harmony, affectivity and communication. Key words: addiction, internet, family, functionality, adolescent